2005
DOI: 10.1007/s00213-005-0117-1
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of vitamin C with atypical antipsychotics reduces oxidative stress and improves the outcome of schizophrenia

Abstract: Oral supplementation of vitamin C with atypical antipsychotic reverses ascorbic acid levels, reduces oxidative stress, and improves BPRS score, hence both the drugs in combination can be used in the treatment of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 23 publications
2
71
0
2
Order By: Relevance
“…Arvindakshan et al (2003) demonstrated that there was a significant reduction in the clinical signs of SZ and an increase in the quality of life of schizophrenic patients that were supplemented with AA combined with D-tocopherol and omega 3 twice a day for a period of 4 months. Another study conducted by Dakhale et al (2005) evaluated the effects of AA supplementation in schizophrenic patients treated with atypical antipsychotics for a period of eight weeks, and found that there was a reduction in the levels of oxidative damage, as well as an improvement in the scores on the Brief Psychiatric Rating Scale of SZ. A recent study has also shown that supplementation with AA (5 mg/l) decreased the effects of neurotoxicity induced by aluminum by reducing the damage within neurotransmitters (serotonin, norepinephrine, dopamine), so decreasing the levels of apoptosis and restoring the morphology of the brain tissue in Nile catfish (Khalili and Hussein 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Arvindakshan et al (2003) demonstrated that there was a significant reduction in the clinical signs of SZ and an increase in the quality of life of schizophrenic patients that were supplemented with AA combined with D-tocopherol and omega 3 twice a day for a period of 4 months. Another study conducted by Dakhale et al (2005) evaluated the effects of AA supplementation in schizophrenic patients treated with atypical antipsychotics for a period of eight weeks, and found that there was a reduction in the levels of oxidative damage, as well as an improvement in the scores on the Brief Psychiatric Rating Scale of SZ. A recent study has also shown that supplementation with AA (5 mg/l) decreased the effects of neurotoxicity induced by aluminum by reducing the damage within neurotransmitters (serotonin, norepinephrine, dopamine), so decreasing the levels of apoptosis and restoring the morphology of the brain tissue in Nile catfish (Khalili and Hussein 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies developed by Zhang et al(2001a; indicated that ginkgo biloba adds haloperidol attribute to chronic or resistant schizophrenia. And supplementation of vitamin C with atypical antipsychotics can reduce oxidative stress and improve the outcome of schizophrenia (Dakhale et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Serum Thiobarbituric Acid Reacting Substances (TBARS) was selected as marker of oxidative stress induced lipid peroxidation. As ascorbate was found to play the role of chief antioxidant in the brain in several studies (13), plasma ascorbate was selected as the indicator for antioxidant activity. Thirty properly matched healthy persons meeting the inclusion/ exclusion criteria were also assessed for serum TBARS and plasma ascorbate.…”
Section: Methodsmentioning
confidence: 99%